2022
DOI: 10.1186/s12966-022-01263-7
|View full text |Cite
|
Sign up to set email alerts
|

Fair play? Participation equity in organised sport and physical activity among children and adolescents in high income countries: a systematic review and meta-analysis

Abstract: Background Physical activity and sport have numerous health benefits and participation is thought to be lower in disadvantaged children and adolescents. However, evidence for the disparity in physical activity is inconsistent, has not been reviewed recently, and for sport has never been synthesised. Our aim was to systematically review, and combine via meta-analyses, evidence of the socioeconomic disparities in physical activity and sport participation in children and adolescents in high income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
36
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 65 publications
0
36
1
Order By: Relevance
“…Sports team participation has been associated with increased levels of physical activity (1) and improved physical and mental health among children and adolescents (2,3). Disparities in sports participation have been found across age, sex, race, disability, and socioeconomic subgroups (4)(5)(6). This report describes national estimates of parent-reported organized sports participation during the past 12 months among children aged 6-17 years.…”
mentioning
confidence: 98%
“…Sports team participation has been associated with increased levels of physical activity (1) and improved physical and mental health among children and adolescents (2,3). Disparities in sports participation have been found across age, sex, race, disability, and socioeconomic subgroups (4)(5)(6). This report describes national estimates of parent-reported organized sports participation during the past 12 months among children aged 6-17 years.…”
mentioning
confidence: 98%
“…Socioeconomic factors were not directly associated with sports participation and physical activity. Previous studies have shown that adolescents demonstrate weaker association between socioeconomic factors and sports participation and physical activity duration than preschool children [ 13 ]. In Japan, most secondary school students belong to school activity clubs, which are generally scheduled after school.…”
Section: Discussionmentioning
confidence: 99%
“…Socioeconomic status (SES), such as parents' income and education level, is one of the factors that influences adolescents' sports participation and physical activity [10][11][12][13]. Adolescents with low SES are less likely to participate in sports and to engage in physical activity than adolescents with high SES.…”
Section: Introductionmentioning
confidence: 99%
“…Studies reporting dropout from long-term PA programmes show that people with low education and socioeconomic status have a higher prevalence than their counterparts [14]. Moreover, a previous qualitative study identified that not only social inequity [32,33] but also having non-negotiable kinship needs (e.g. family care) may effect treatment adherence [34].…”
Section: Introductionmentioning
confidence: 99%
“…political decision-making) may have more influence on PA routinization than patients' motivation and knowledge [34,36]. Yet, ineffective primary care-based PA recommendations may enhance socioeconomic barriers and health inequity in T2DM patients [32,33].…”
Section: Introductionmentioning
confidence: 99%